Computation of magnetic characteristics for the double rotor switched reluctance motor using flux tube analysis. - Vaithilingam, Chockalingam Aravind; Misron, Norhisam; Raja Othman, Raja Nor Firdaus Kashfi; Aris, Ishak; Marhaban, Mohammad Hamiruce; Nirei, Masami (2012)
The introduction of the oscillatory torque inside the reluctance machine during its operation with the reduction the air-gap length is a major tumble it as a high torque density machine. A double rotor structure that embeds the dual air gap structure to maximize the flux linkage and thereby the torque generating capability is proposed. For efficient operation the machine needs to operate close to saturation, and hence the estimation of magnetic and mechanical parameters is extremely cumbersome. Electromagnetic analysis of different positions on the machine to develop the flux linkage characteristics of the double rotor structure is presented. Pertaining equations of calculations for the magnetic components of the full overlap, partial overlap and full non-overlap positions are presented. The mechanical torque characteristics obtained from this analytical computation method is compared with that of the finite element analysis. The proposed technique of electromagnetic analysis can be applied to any type of electrical machine.